Indonesian Voting from Abroad: Highly Educated Citizen Participation in the 2019 Election at Tokyo Polling Station - Sri Endah Pujiatin (Pusbindiklatren Bappenas, 2021)
The political rights of Indonesian citizens living abroad have been guaranteed by law since 1953 and implemented by a joint committee between the General Election Commission and the Ministry of Foreign Affairs. As a developing country with increasing democracy, Indonesia’s external voting needs to be studied. Using the qualitative analysis of macro data and questionnaire survey in Tokyo, this study addresses the following questions: How is the implementation of external voting by the Indonesian government? How is the voter? How does the registration, administration, voting facilitation, and voting method influence voter participation in home country elections? The findings suggest that the government provides many resources to facilitate external voting. Nevertheless, survey results revealed that some facilitation was inadequate compare to the number of voters. Although highly educated citizens tend to have a high awareness of home country elections, problems in voting facilitation might prevent them from voting.